Justice for English-speaking Quebecers - Alliance Quebec (AQ) (1999)

Adoption of Seven Health and Social Services Access Plans : Too Little Too Late - Alliance Quebec (AQ) (1999)

Statement by William Johnson, President of Alliance Quebec in Reply to an Attack by Gary Richards, President of the Townshippers' Association - Johnson, William (1999)

Alliance Quebec Goes At Last to Court to Force the Government to Approve Long Overdue English Health Services - Alliance Quebec (AQ) (1999)

Statement by Alliance Quebec President William Johnson on Applying for a Writ of Mandamus to Force the Quebec Government to Approve Access Plans to English Health and Social Services - Alliance Quebec (AQ) (1999)

Newsletter - The Centre for Literacy of Quebec (CFL) (1999)

[Letter from William Johnson, President of Alliance Quebec, to Hon. Lucien Bouchard, Premier of Quebec] - Johnson, William (1998)

An Outlaw Government - Alliance Quebec (AQ) (1998)

Alliance Quebec Demands that People Receive Health and Social Services in the Language They Choose to Use - Alliance Quebec (AQ) (1997)

Le discours de Lucien Bouchard au Centaur - Un an plus tard, un bilan - Alliance Quebec (AQ) (1997)

The Centaur Speech - One Year Later - Alliance Quebec (AQ) (1997)

Alliance-Quebec Condemns Language Bureaucrats' Involvement in Health Care - Alliance Quebec (AQ) (1997)

Alliance Quebec Petitions Information Commission for Answers on OLF Health Report - Alliance Quebec (AQ) (1997)

Alliance Québec réclame que les gens reçoivent des services sociaux et de santé dans la langue de leur choix - Alliance Quebec (AQ) (1997)

Alliance Québec : Une nouvelle étude sur la langue vise-t-elle les institutions anglophones et les gens qui y travaillent? - Alliance Quebec (AQ) (1996)

Coasters Association Informer - Coasters Association (1994)

Working Papers on English Language Institutions in Quebec - Schachter, Susan (Alliance Quebec (AQ), 1982)
This project was designed to provide a resource for Quebec's English-speaking community and others who feel the need for information about themselves and those institutions usually identified as "English". The decision that such a resource was needed was based on both objective and subjective criteria. Objectively, the English-speaking population of Quebec is, and always has been, an unstable one; that is, large numbers of English-speaking people have always been among those moving to and from the province, Ieaving behind a relatively small core of their fellows with deep roots in Quebec. This high turn-over in population has affected the continuity of the English-speaking community. Such a state of fluidity has made it difficult to evolve a distinctive English-speaking cultural identity with Quebec as its focal point. On the other hand, it has Ied to a discontinuity in the knowledge of our economic, political and cultural role in Quebec. Hence, the need for a resource such as this.